Tazkiyah al-Nafs in Al-Ghazali’s Thought: A Sufi Framework for Enhancing Mental Resilience among Generation-Z - Ahmad Farid Fanani; Rifat Syauqi Efendi; Shofiyullah Muzammil (University of Darussalam Gontor, Indonesia, 2026)
Generation Z, often referred to as the “Strawberry Generation,” is characterized by marked psychological vulnerability arising from social pressures and intensive digital exposure. This condition requires an approach that is not only technical but also spiritual, such as the concept of tazkiyah al-nafs in Islamic teachings. Accordingly, this study aims to analyze the potential of tazkiyah al-nafs as a mental resilience strategy for Generation Z based on al-Ghazali’s thought. This research employs a qualitative approach using the library research method with content analysis techniques. The data sources include Ihya’ ‘Ulum al-Dīn, scientific articles, and thematic books related to tazkiyah al-nafs and mental health. The findings indicate that tazkiyah al-nafs provides a systematic spiritual framework for cultivating mental resilience. The stage of takhallī teaches the release of blameworthy traits such as anger, envy, and worldly attachment, which often constitute the roots of emotional instability. Taḥallī instills virtues such as patience, gratitude, trust in God, and humility, which strengthen psychological stability and foster a sense of life meaning. Meanwhile, tajallī represents a phase of spiritual illumination in which individuals attain inner peace and profound transcendental awareness. Collectively, these three stages enhance coping capacity and establish a holistic structure of long-term resilience. This study contributes to integrating Sufi values into the framework of modern Islamic psychology while expanding the discourse on spiritual interventions as concrete solutions to mental health challenges among young generations.